Genitogluteal porokeratosis: a clinical review - Joshi R; Minni K (Dove Medical Press, 2018)
Rajiv Joshi,1 Khushboo Minni2 1Department of Dermatology, P. D. Hinduja Hospital, Mumbai, India; 2Department of Dermatology, Mumbai Port Trust Hospital, Mumbai, India Abstract: Porokeratosis is an uncommon disorder of keratinization that presents with keratotic papules or annular plaques that expand centrifugally with a thread-like elevated border. A distinctive histologic structure, the cornoid lamella, is diagnostic of this disorder and consists of a column of parakeratosis with the absence of the granular layer and dyskeratotic cells in the upper spinous zone. Porokeratosis confined to the genitogluteal region is rare and may be subclassified into three types, namely, classical porokeratosis on the genital region, ptychotropic porokeratosis most often seen in the natal cleft and buttocks and penoscrotal porokeratosis that is seen on the penis and adjacent scrotal skin in young men in their third decade of life. Genitogluteal porokeratosis is usually pruritic and may be undiagnosed for several years as it does not resemble classical porokeratosis in many cases; however, a biopsy is diagnostic. In general, response of genital porokeratosis to any modality of treatment is disappointing. No malignant changes have hereto been reported in porokeratosis restricted to the genitogluteal region. Keywords: genital porokeratosis, ptychotropic porokeratosis, penoscrotal porokeratosis